"Si Dios Quiere:" Instability, Sustainability, and Wellness in a Vermont Migrant Worker Health Clinic. (3rd December 2020) - Smith, Kelsey
Abstract: The political health ecology of Vermont is shaped by its status as a rural, borderland state and its dependence upon dairy for agricultural revenue in a fluctuating neoliberal market. The Care Center, a free clinic serving uninsured patients in Cherry County, is the primary medical provider for the growing Latinx migrant worker population that supports the majority of Vermont dairy farms. My findings demonstrate the gendered nature of how Latinx migrant dairy workers and healthcare professionals navigate the compounding precarities in Vermont that make safety and wellness difficult to establish. I contend that the layered use of structural vulnerability, political health ecology, and ecofeminist situated sustainability offers a perspective on the hidden interconnectedness between healthcare work and sustainability, ultimately providing directions for collaboration.